Effect of herbal product on the body weight reduction in high fat diet-induced obese Sprague Dawley Rats / Chai Swee Fern - Chai , Swee Fern (2018)
The aim of this study was to determine the effect of herbal product (HP) on the body weight reduction and lipid profile improvement in high fat diet (HFD)-induced obese Sprague Dawley (SD) rats. The ethyl acetate fraction (EAF) showed the highest total phenolic content (TPC) and total flavonoid content (TFC) at 30.48 ± 0.62 mg GAE/g and 156.52 ± 3.13 mg QE/g, respectively. It also showed the highest antioxidant capabilities to scavenge 2,2-diphenyl-1-picrylhydrazyl (DPPH) at IC50 = 0.03 ± 0.00 mg/mL, nitric oxide (NO) at IC50 = 1.00 ± 0.05 mg/mL and superoxide at IC50 = 0.16 ± 0.01 mg/mL and reduce ferric ions at 109.27 ± 3.35 μmol Fe2+/g. However, the EAF showed low capability in chelating metal (< 50%). The oral acute toxicity test of the HP extract at a single dose of 5 g/kg body weight of rat showed no mortality and no toxic effect on SD rats. The body weight of HFD rats after two weeks treatment with water extract (WE), simvastatin and EAF was significantly reduced by 4.79%, 6.18% and 6.64%, respectively (p < 0.05). The body mass index (BMI) of the HFD rats after two weeks treatment with WE, simvastatin and EAF was also significantly reduced (p < 0.05). The treatment of HFD rats with EAF also led to significant reductions on triglyceride (TG), total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C), with a positive elevation of high density lipoprotein cholesterol (HDL-C) compared to WE and simvastatin. In conclusion, the results showed that the EAF had better potential for body weight reduction and lipid profile improvement in HFD rats than WE and simvastatin.